HERBICIDE SELECTIVITY IN PREEMERGENCE OF SWEET SORGHUM CULTIVATED IN DIFFERENT SOIL TEXTURE - SANTOS LIMA, MARIUCÉLIO; QUERNE DE CARVALHO, CAIO; PADOVESE, LUCAS MATHEUS; INOJOSA FERREIRA, LUIZ AUGUSTO; OLIVERIA JUNIOR, RUBÉM SILVÉRIO DE; BIFFE, DENIS FERNANDO (International Journal of Maize & Sorghum, 2020)
Sweet sorghum (Sorghum bicolor (L.) Moench) is an interesting alternative for biomass and ethanol production, however, so far there is very limited knowledge regarding selective herbicide options for weed control in this crop. The objective of this study was to evaluate the selectivity of preemergence herbicides for sweet sorghum. This research was composed by two steps: in the first one, a greenhouse screening was carried out with several herbicide treatments and in the following step the most selective treatments were evaluated on field conditions. In sandy clay loam texture soil, the treatments involving atrazine (1000 and 2000 g ha-1), amicarbazone (210 g ha-1), trifluralin (500 g ha-1) and flumioxazin (25 g ha-1) provided the greatest levels of selectivity to sweet sorghum. In clay soil (64.7% clay), the treatments with atrazine (1000, 1500 and 2000 g ha-1), amicarbazone (280 g ha-1), S-metolachlor (480 g ha-1), [atrazine + S-metolachlor] ([601+471,2 g ha-1), pendimethalin (500 g ha-1) and imazethapyr (42.4 and 63.6 g ha-1) provided the lowest levels of crop injury, and were considered as the most selective for sweet sorghum. Herbicide treatments applied to sandy clay loam soil provided more injuries to sweet sorghum than those applied to clay soil.